Asthma control in adults in the Middle East and North Africa: Results from the ESMAA study. (May 2018) - Tarraf, Hesham; Al-Jahdali, Hamdan; Al Qaseer, Abdul Hameed; Gjurovic, Anamarija; Haouichat, Houria; Khassawneh, Basheer; Mahboub, Bassam; Naghshin, Roozbeh; Montestruc, François; Behbehani, Naser
Abstract: Background: Low levels of asthma control are reported in many countries worldwide. Improved knowledge of asthma control in the Middle East and Africa and predictive factors is needed to address this major public healthcare burden. Objective: To assess the level of asthma control in patients attending a routine consultation for asthma in the Middle East and North Africa, and the relationship between level of control and patient and disease characteristics, adherence, and quality of life (QoL). Methods: A large-scale cross-sectional epidemiological study (ESMAA: Assessment of Asthma Control in Adult Asthma Population in the Middle East and North Africa) was performed in adults suffering from asthma for at least 1 year and without an acute asthma episode within 4 weeks. Asthma control was assessed per the 2012 GINA guidelines and the ACT questionnaire. QoL and adherence were assessed with the SF-8 and Morisky questionnaires respectively. Predictive factors of asthma control were analysed with univariate and multivariate logistic regressions analyses. Results: Overall 7236 eligible patients were included in 577 sites between June 2014 and December 2015 (median 10 patients/site). Mean age was 45 years (±14), 57% were female, mean BMI was 28.5 kg/m 2 (±6.0), and 11% were active smokers. Reliever medication was prescribed in 96% of patients with 65% having fixed-dose combined inhaled corticosteroid plus long-acting beta agonists. Good medication adherence was reported in 24% of patients. Among 7179 patients evaluable for GINA, asthma was controlled in 29.4% (95% CI, 28.4%–30.5%), partly controlled in 29.1% (95% CI, 28.1%–30.2%), and uncontrolled in 41.5% (95% CI, 40.3% to 42.6). The mean global ACT score was 17.8 (±5.0), with 16% of patients considering their asthma as controlled. Poor medication adherence, active smoking, absence of medical insurance, lower level of education, or diagnosis at least 5 years earlier were significantly associated with uncontrolled asthma in multivariate analyses (p < 0.001). Conclusions: Asthma control in the Middle East and North Africa is unsatisfactory with less than one-third of asthma patients having controlled disease, highlighting the need to improve treatment access and medication adherence, along with better follow-up and education among healthcare providers and patients. Highlights: Asthma was controlled in 29% of a large Middle East/North African population. Poor medication adherence, smoking, no medical insurance are linked to poor control. Asthma control is unsatisfactory in Middle Eastern and North African adults. Better access to treatment, proactive follow-up and education are needed.